Choosing treatment options for patients with relapsed/refractory multiple myeloma. Issue 2 (February 2014) - Castelli, Roberto; Orofino, Nicola; Losurdo, Agnese; Gualtierotti, Roberta; Cugno, Massimo
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) is a clonal plasma cell disorder that is still incurable using conventional treatments. Over the last decade, advances in front-line therapy have led to an increase in survival, but there are still some doubts in the case of relapsed/refractory disease. We searched the PubMed database for articles on treatment options for patients with relapsed/refractory MM published between 1996 and 2013. These treatments included hematopoietic cell transplantation (HCT), rechallenges using previous chemotherapy regimens, and trials of new regimens. The introduction of new agents such as the immunomodulatory drugs (IMIDs) thalidomide and lenalidomide, and the first-in-its-class proteasome inhibitor bortezomib, has greatly improved clinical outcomes in patients with relapsed/refractory MM, but not all patients respond and those that do may eventually relapse or become refractory to treatment. The challenge is therefore to select the optimal treatment for each patient by balancing efficacy and toxicity. To do this, it is necessary to consider disease-related factors, such as the quality and duration of responses to previous therapies, and the aggressiveness of the relapse, and patient-related factors such as age, comorbidities, performance status, pre-existing toxicities and cytogenetic patterns. The message from the trials reviewed in this article is that the new agents may be used to re-treat relapsed/refractory disease, and that the sequencing of their administration should be modulated on the basis of the various disease and patient-related factors. Moreover, our understanding of the pharmacology and molecular action of the new drugs will contribute to the possibility of developing tailored treatment.